Impulsivity and drinking motives predict problem behaviours relating to alcohol use in University students - Jones, Katy A.; Chryssanthakis, Alexandra; Groom, Madeleine J. (Elsevier, 2014)
Aims: This study used a four-factor model of impulsivity to investigate inter-relationships between alcohol consumption, impulsivity, motives for drinking and the tendency to engage in alcohol-related problem behaviours. Methods: 400 University students aged 18-25 completed an online survey consisting of the following measures: Urgency, Premeditation, Perseverance and Sensation Seeking Scale (UPPS) to measure impulsivity; Student Alcohol Questionnaire to assess drinking quantity, frequency and rates of problem behaviours; Drinking Motives Questionnaire to assess motives for drinking. Results: The majority of the sample (94.5%) drank alcohol at least monthly. Path analysis revealed direct effects of urgency, sensation seeking and premeditation, as well as the quantity of alcohol consumed, on the tendency to engage in risky behaviours with negative consequences. The effect of urgency was mediated by drinking for coping motives and by a combined effect of drinking for social motives and consumption of wine or spirits. Conversely the effect of sensation seeking was mediated by the quantity of alcohol consumed, irrespective of drink type, and the effect of premeditation was mediated by the consumption of wine and spirits, in combination with enhancement motives. Conclusions: Sensation seeking, urgency and lack of premeditation are related to different motives for drinking and also demonstrate dissociable relationships with the consumption of specific types of alcohol (beer, wine and spirits) and the tendency to engage in risky behaviours associated with alcohol consumption. Screening for high levels of urgency and for severe drinking consequences may be useful predictors of alcohol-related problems in UK University students aged 18 to 25 years.